The Hairdex quality of life instrument-A translation and psychometric validation in patients with alopecia areata - Johan Fhager; Åke Svensson; Karin Örmon; Tobias W. Fischer; Karin Sjöström (Wiley, 2023)
Abstract Background The German Hairdex quality of life (QoL) instrument is specific to hair and scalp diseases, developed for self‐rating and consists of 48 statements divided into five domains: Symptoms, Functioning, Emotions, Self‐confidence and Stigmatisation. There was a need of a Swedish reliability tested, validated hair and scalp specific QoL instrument why the German Hairdex was chosen to be translated and reliability tested in a systematic way. Objectives To make a translation, a reliability test of stability, and validation of the German Hairdex QoL instrument among 100 Swedish patients with a dermatological ICD‐10 diagnosis of alopecia areata (AA). Methods An eight‐step method by Gudmundsson was used as a model with a forward and backward translation and with comments from an expert panel. A statistical test-retest (ICC (2,1)) analysis was made, followed by an internal consistency analysis. A comparison between the German and Swedish Hairdex‐S constructs by a principal component analysis was performed. Results The Hairdex‐S was very well accepted by patients. The ICC(2,1) test-retest showed a good to excellent correlation of 0.91 (CI [0.85-0.95]). Internal consistency was α = 0.92. Like the original Hairdex, Hairdex‐S showed good factorability with a Kaiser-Meyer-Olkin measure of 0.82 and with one component explaining 70% of the variance: original Hairdex instrument (69%). When tested on patients with AA, the domains Functioning and Emotions had the strongest loadings, followed by Stigmatisation and Self‐confidence. Younger AA patients at self‐assessment and patients who reported to be younger at the onset of AA, scored statistically significantly higher on the Hairdex‐S, indicating an overall lower QoL on domains Emotions and Functioning, respectively. Conclusions The Hairdex‐S is very well accepted by AA patients, shows very good psychometric properties, and a very good agreement with the original Hairdex. The Swedish Hairdex instrument can be recommended for evaluation of patients QoL as well as for research purposes.